Avoiding big bubble complications: outcomes of layer-by-layer deep anterior lamellar keratoplasty in children. Issue 8 (4th January 2018) - Elbaz, Uri; Kirwan, Caitriona; Shen, Carl; Ali, Asim
Abstract : Background/aims: To describe the visual and clinical outcomes of manual layer-by-layer deep anterior lamellar keratoplasty (DALK) in a paediatric population. Methods: The charts of all children who underwent DALK surgery between January 2007 and January 2015 were reviewed retrospectively. Data collected included preoperative and postoperative spectacle-corrected distance visual acuity (CDVA), intraoperative and postoperative complications including graft rejection and failure. Residual posterior lamellar thickness (RPLT) and endothelial cell density (ECD) were measured in eyes with follow-up longer than 6 months. Results: Fifty-one eyes of 42 patients were included in the study. The mean patient age at surgery was 11.2±5.2 years and the mean follow-up time was 36.5±23.7 months. The most common indications for surgery were mucopolysaccharidosis (29.4%) and keratoconus (23.5%). Nine eyes (17.6%) had intraoperative microperforation, none of which were converted to penetrating keratoplasty (PKP). Only one eye (2.0%) was converted to PKP. Five eyes (9.8%) had a stromal rejection episode of which one eye failed. Another four eyes (7.8%) experienced graft failure among which three eyes (75%) had infectious keratitis. Three of the five failed grafts had a successful repeat DALK. The average RPLT was 81.9±36.5μm. ECD was significantly lower in the operated eye compared with the normal eye (3096±333 cells/mm 2 vs 3376±342 cells/mm 2, n=11, P=0.003). The mean postoperative CDVA was 0.5±0.4 logarithm of the minimum angle of resolution (logMAR) reflecting a gain of 0.3 logMAR (P<0.001). Conclusion: Manual dissection DALK is a safe procedure in children with stromal opacities. Despite successful structural rehabilitation, functional recovery is still suboptimal mostly due to amblyopia.